Electrolyte and battery provided with electrolyte
By forming a bridge structure in the electrolyte, the conductivity of lithium ions is improved by using the alternating arrangement of the medium and the metal salt, the problem of insufficient ion conductivity of the existing electrolyte is solved, and the ion conductivity and performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202380038411.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-02
- Filing Date
- 2023-07-21
- Publication Date
- 2024-12-20
AI Technical Summary
There is room for improvement in the ion conductivity of existing electrolytes, especially in lithium-ion batteries, which affects the performance of the battery.
By forming a bridge structure in the pores of the porous insulator, a media with two nitrile groups and a metal salt are alternately arranged to form a bridge structure to improve the conductivity of metal ions. The molar ratio of the media to the metal salt is controlled between 0.1 and 4.0 between.
It significantly improves the ion conductivity of the electrolyte, achieves higher ion conductivity, and improves the performance of the battery.
Smart Images

Figure CN119174024A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrolyte and a battery having the electrolyte. Background Art
[0002] Batteries include air batteries, fuel cells, and secondary batteries, and are used for various purposes. Batteries include a positive electrode and a negative electrode, and an electrolyte that is responsible for ion transport between the positive electrode and the negative electrode.
[0003] For example, Patent Document 1 discloses an ion conductive composite (electrolyte) comprising: an insulating structure composed of a porous coordination polymer having unsaturated sites for metal salt coordination; and a porous coordination polymer having an insulating structure composed of [R-SO2-N-SO2-R'] - (R and R' represent fluorine atoms or fluoroalkyl groups); and metal cations (such as Li + 、Na + or Mg 2+ ).
[0004] In addition, Patent Document 2 discloses an electrolyte regulating substance that can be used in metal batteries, comprising a liquid electrolyte and a metal-organic structure (MOF) material, wherein the metal-organic structure (MOF) is incorporated into the liquid electrolyte to form a MOF slurry electrolyte. MOF is a type of crystalline porous solid constructed by metal cluster nodes and organic connectors, and can bind anions, remove ion pairs, and improve cation transport during activation and impregnation of the liquid electrolyte.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 6222635
[0008] Patent Document 2: Japanese Patent Application No. 2020-508542 Summary of the invention
[0009] Technical problem to be solved by the invention
[0010] The present inventors have noticed that the above-mentioned electrolytes still have technical problems to be overcome, and have found that it is necessary to take countermeasures. Specifically, as a technical problem, the present inventors have found that there is room for improvement in the ion conductivity of the electrolyte.
[0011] The present disclosure has been made in view of the above-mentioned technical problems. That is, the main object of the present disclosure is to provide an electrolyte having better ion conductivity than conventional electrolytes.
[0012] Technical solutions for solving technical problems
[0013] The present inventors have attempted to solve the above technical problems by taking measures in a new direction instead of extending the existing technology. As a result, they have completed the invention of an electrolyte that achieves the above main purpose.
[0014] An electrolyte according to one embodiment of the present disclosure,
[0015] A porous insulator having pores, a medium having two nitrile groups and a metal salt arranged in the pores,
[0016] The metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts,
[0017] The molar ratio of the medium to the metal salt (medium / metal salt) is 0.1 or more and 4.0 or less.
[0018] In addition, a battery according to one embodiment of the present disclosure,
[0019] The above-mentioned electrolyte is provided.
[0020] Effects of the Invention
[0021] The present disclosure can provide an electrolyte having better ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a conceptual diagram showing an example of a battery according to the second embodiment of the present disclosure.
[0023] Figure 2 This is a graph showing the relationship between the molar ratio (SN / LiFSI) and the ion conductivity at room temperature.
[0024] Figure 3 The electrolytes of Examples 2 to 3, Examples 5 to 7 and Comparative Example 1 have a range of 2220 to 2320 cm -1 Raman spectrum of . DETAILED DESCRIPTION
[0025] Hereinafter, the "electrolyte" and the "battery" having the electrolyte of the present disclosure will be described in detail through the embodiments. Although the description is made with reference to the drawings as needed, the contents of the drawings are only schematically and exemplarily shown for the purpose of understanding the present disclosure, and the appearance and dimensional ratios may be different from the actual objects.
[0026] The various numerical ranges mentioned in this specification are intended to include the lower and upper limits themselves, unless otherwise specified, such as "less than," "smaller," and "larger." That is, if a numerical range of 1 to 10 is taken as an example, it is interpreted as including the lower limit 1 and also including the upper limit 10.
[0027] In this specification, "the object part is substantially composed of a specific material" or "the object part is composed of a specific material" means that the object part contains the specific material in a ratio of 95 mass %, 97 mass %, 99 mass %, or 100 mass %. For example, "mesoporous silica is substantially composed of silicon dioxide (SiO2)" means that the mesoporous silica contains silicon dioxide (SiO2) in a ratio of 95 mass %, 97 mass %, 99 mass %, or 100 mass %.
[0028] In the present disclosure, a "battery" refers in a broad sense to a device that can extract energy by electrochemical reaction. In a narrow sense, a "battery" refers to a device that has a pair of electrodes and an electrolyte, and in particular, is charged and discharged with the movement of ions. Although it is only an example, as a battery, for example, a primary battery and a secondary battery can be listed, more specifically, a lithium battery, a magnesium battery, a sodium battery, and a potassium battery.
[0029] In the present disclosure, unless otherwise specified, the "electrolyte solution" refers to an electrolyte solution obtained by removing a porous insulator from the electrolyte involved in the present disclosure, and refers to an electrolyte solution composed of a metal salt and a dielectric.
[0030] <First embodiment: electrolyte>
[0031] The electrolyte according to the first embodiment of the present disclosure is used in, for example, a battery. That is, the electrolyte described in this specification corresponds to an electrolyte used in a device that can extract energy by electrochemical reaction.
[0032] As a premise, the electrolyte involved in the first embodiment is an electrolyte for a battery having an electrode composed of lithium, magnesium, sodium or potassium. In particular, it is an electrolyte for a battery having a lithium electrode as a negative electrode. Therefore, the electrolyte involved in the first embodiment can also be said to be an electrolyte for a lithium electrode-based battery (hereinafter, also referred to as a "lithium electrode-based electrolyte").
[0033] Here, the "lithium electrode" used in this specification refers to an electrode having lithium (Li) as an active ingredient (i.e., an active material) in a broad sense. In a narrow sense, a "lithium electrode" refers to an electrode comprising lithium, for example, an electrode comprising lithium metal or a lithium alloy, and in particular, a negative electrode of such lithium. It should be noted that the lithium electrode may contain components other than lithium metal or lithium alloy, but in a preferred embodiment, it is an electrode composed of a metal body of lithium (for example, an electrode composed of a monomer of lithium metal having a purity of 90% or more, preferably a purity of 95% or more, and more preferably a purity of 98% or more).
[0034] The electrolyte according to the first embodiment has Li ion conductivity in the case of a lithium electrode system. The ion conductivity of the electrolyte according to the first embodiment is, for example, 10 -4 The method for measuring the ion conductivity is described in detail in the examples.
[0035] The electrolyte according to the first embodiment,
[0036] A porous insulator having pores, a dielectric (dielectric molecule) having two nitrile groups (cyano group; -CN group) arranged in the pores, and a metal salt,
[0037] The metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts,
[0038] The molar ratio of the medium to the metal salt (medium / metal salt) is 0.1 or more and less than 0.8 and 0.8 or more and 4.0 or less (ie, 0.1 or more and 4.0 or less).
[0039] [Mechanism of action]
[0040] The electrolyte involved in the present embodiment has better ion conductivity. Although not limited to a specific theory, the reasons are speculated as follows. In the electrolyte involved in the present embodiment, the metal salt and the medium can form a bridge structure in a specific molar ratio (medium / metal salt=0.1~4.0). In detail, the electrolyte involved in the present embodiment can adopt a bridge structure in which the medium and the positive ions (more specifically, metal ions) constituting the metal salt are alternately arranged. If the bridge structure is arranged in the pores of the porous insulator, a part of it has defects (holes) where metal ions are missing, so it can become a path for effectively transporting metal ions in the electrolyte. Therefore, in the electrolyte involved in the present embodiment, the above-mentioned bridge structure is formed, so the ion conductivity of the metal ions becomes higher.
[0041] (Bridge Structure)
[0042] In the bridge structure, the medium and the positive ions (metal ions) constituting the metal salt are arranged alternately, and a part of the metal ions is missing. Referring to [Chemical Formula 1],
[0043] [Chemical Formula 1]:
[0044]
[0045] The bridge structure is described in detail. In [Chemical Formula 1], as an example of the electrolyte involved in this embodiment, a porous insulator containing succinonitrile as a medium and metal ions Li + The electrolyte composed of metal salt (succinonitrile-Li +In the case of succinonitrile-Li + In the electrolyte of the system, the bridge structure has the nitrile group (nitrogen atom) of succinonitrile and Li + Coordination, succinonitrile and Li + Alternately arranged in one dimension, some Li + Missing defects (dashed circles in [Chemical Formula 1]). + When observing the bridge structure from an angle, in the bridge structure, the adjacent Li + In addition, due to the presence of Li + defects, so the adjacent Li + can move to the defect via succinonitrile. + Since the metal ions can sequentially move within the bridge structure, it is considered that the bridge structure contributes to the efficient transport of metal ions within the electrolyte, thereby achieving more excellent ion conductivity.
[0046] It should be noted that in the bridge structure, the one-dimensional arrangement refers to, for example, succinonitrile and Li + Arranged in a straight chain. However, succinonitrile and Li + The arrangement of is not limited to this. For example, succinonitrile and Li + The arrangement may be two-dimensional or three-dimensional, and more specifically, the linear arrangement may be bent or branched.
[0047] (Bridge structure confirmation method)
[0048] The bridge structure can be confirmed by structural analysis based on Raman spectroscopy. As described above, the bridge structure can be constructed by the coordination of the metal ions of the metal salt and the medium. That is, the bridge structure can be constructed by forming a coordination bond between the metal ions and the specific functional groups of the medium. Therefore, by using micro-Raman spectroscopy to confirm that "the peak of the specific vibration of the functional group derived from the coordinated bond is shifted to the high wave number side compared to the peak of the specific vibration of the functional group derived from the uncoordinated state", the existence of the bridge structure can be confirmed.
[0049] For example, in the above-mentioned succinonitrile (SN)-Li + In the electrolyte of the system, its presence can be confirmed by confirming that "in the Raman spectrum, the peak of the CN stretching vibration of the nitrile group originating from the medium (Raman scattering peak) is shifted to the high wave number side" by using micro Raman spectroscopy. Although the stretching vibration of the CN of the nitrile group in the state coordinated with the metal ion is shifted to the high wave number side compared with the peak (known peak) of the stretching vibration of the CN of the nitrile group in the state not coordinated with the metal ion, it can be confirmed.
[0050] The method for confirming the bridge structure is described in detail in the examples.
[0051] (The reason for proposing this disclosure)
[0052] When the electrolyte used in lithium ion batteries is impregnated in a porous insulator, the ion conductivity is still low. The inventors have conducted in-depth research on the concept of improving the ion conductivity. As a result, it was found that by forming a bridge structure in the pores, the metal ions propagate in the bridge structure in the pores, and the ion conductivity becomes higher than the mechanism in which only the metal ions propagate in the pores in a solvated state. As a result, the inventors thought of the electrolyte involved in this embodiment that improves the ion conductivity by a completely new mechanism that is not in the previous concept of carrier transport by the bridge structure.
[0053] (Molar ratio (medium / metal salt))
[0054] The molar ratio of the medium to the metal salt (medium / metal salt) is 0.1 or more and 4.0 or less. When the molar ratio is less than 0.1 or greater than 4.0, the ionic conductivity is reduced. From the viewpoint of further improving the ionic conductivity of the electrolyte, the lower limit of the molar ratio is preferably 0.2, more preferably 0.3, and the upper limit of the molar ratio is preferably 2.0, more preferably 1.5, further preferably 1.2, and particularly preferably 1.0. By arbitrarily selecting and combining from a plurality of preferred numerical ranges, it is possible to set the preferred numerical range of the molar ratio (the numerical range comprising the upper limit and the lower limit). For example, the molar ratio is preferably 0.2 or more and 2.0 or less.
[0055] In particular, the molar ratio (SN / LiFSI) is preferably 0.2 to 2.0, and more preferably 0.4 to 1.0.
[0056] ―Method for determining the molar ratio (medium / metal salt)―
[0057] The molar ratio (medium / metal salt) can be determined by the amount of the medium and metal salt added (molar ratio in the raw material state) constituting the electrolyte involved in this embodiment. Alternatively, the molar ratio (medium / metal salt) can also be determined by the electrolyte (as a finished product).
[0058] The electrolyte according to this embodiment may be a solid electrolyte.
[0059] The electrolyte involved in this embodiment includes a porous insulator, a dielectric and a metal salt. The electrolyte involved in this embodiment may further include components other than these components (porous insulator, dielectric and metal salt) within the scope of exerting the main effect of the present disclosure. Below, these components constituting the electrolyte are described.
[0060] (Porous insulator)
[0061] The porous insulator has a medium having two nitrile groups and a metal salt disposed in its pores. Thus, the electrolyte involved in the first embodiment easily forms a bridge structure that contributes to better ion conductivity. The porous insulator has pores. The porous insulator is, for example, at least one selected from the group consisting of zeolite and mesoporous silica.
[0062] From the viewpoint of improving the ionic conductivity of the electrolyte, the porous insulator is preferably zeolite and mesoporous silica. Although not limited to a specific theory, the reason is speculated as follows. In the electrolyte involved in the present embodiment, it can be considered that if the electrolyte is at least one of zeolite and mesoporous silica as a porous insulator (if at least one is included), the silanol group (Si-OH) present in the pore inner wall of the zeolite and mesoporous silica acts as a carrier (positive ions of metal salts, more specifically, Li + More specifically, it is believed that the protons (H + ) is exchanged with the carrier, and the silanol group functions as a hopping site of the carrier. Therefore, if the electrolyte contains at least one of zeolite and mesoporous silica as a porous insulator, the ion conductivity of the electrolyte is further improved.
[0063] In porous insulators, for zeolite and mesoporous silica, from the viewpoint of improving the ionic conductivity of the electrolyte, the Si / Al ratio is, for example, 5 or more, preferably 15 or more, more preferably 40 or more, further preferably 100 or more, particularly preferably 500 or more, and very particularly preferably 1500 or more. In addition, the Si / Al ratio is, for example, 10,000 or less. These upper and lower limits can be arbitrarily combined to form a numerical range (for example, 5 or more and 10,000 or less). In this specification, the Si / Al ratio refers to the molar ratio of Si (silicon atoms) to Al (aluminum atoms) constituting the porous insulator.
[0064] Zeolite and mesoporous silica can have more silanol groups on the inner wall of their pores if the Si / Al ratio is 5 or more. This is because, in this case, more carrier hopping sites can exist on the inner wall of the pores of zeolite and mesoporous silica, and it is believed that the ion conductivity of the electrolyte is further improved.
[0065] The Si / Al ratio of zeolite and mesoporous silica is measured as follows. The zeolite or mesoporous silica is crushed to a degree that can be measured and placed in a nuclear magnetic resonance device ("ECA400 FT-NMR device" manufactured by JEOL Ltd.). At a magnetic field strength of 9.2 T and nuclides: 29 The Si / Al ratio was obtained by measuring under the conditions of Si measurement and obtaining an NMR spectrum.
[0066] It should be noted that the zeolite or mesoporous silica used in the measurement of the Si / Al ratio can be measured not only in the raw material state, but also in the state separated from the finished product (for example, the electrolyte or a battery having an electrolyte (more specifically, the measurement unit cell described later in the examples)).
[0067] Examples of commercially available zeolites include "HS-690", "HS-642" and "HS-320" (cationic species: H or Na) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and "HSZ-360HUA", "HSZ-385HUA", "HSZ-640HOA", "HSZ-840HOA", "HSZ-890HOA" and "HSZ-980HOA" manufactured by Tosoh Corporation. Examples of commercially available mesoporous silicas include "MCM-41", "MCM-48", "SBA-15" and "SBA-16" manufactured by Sigma Aldrich.
[0068] (medium)
[0069] The medium is an electrically neutral molecule. The medium disperses, dissolves or solid-dissolves the metal salt in the electrolyte. The medium is a medium having two nitrile groups (nitrile-based medium). As a nitrile-based medium, for example, at least one selected from the group consisting of succinonitrile (1,2-dicyanoethane), glutaronitrile (1,3-dicyanopropane) and adiponitrile (1,4-dicyanobutane).
[0070] If the medium is at least one of these, it is easy to form a bridge structure with the metal ions constituting the metal salt in the electrolyte. Therefore, in this case, the ion conductivity of the electrolyte involved in this embodiment becomes higher.
[0071] (Metal Salt)
[0072] The metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts. As metal salts, for example, alkali metal salts (more specifically, lithium metal salts, etc.) can be listed. As lithium metal salts, for example, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4) and lithium perchlorate (LiClO4) can be listed. As lithium salts, LiFSI and LiTFSI are preferred, and LiFSI is more preferred. As alkali metal ions constituting alkali metal salts, for example, Li + 、Na + and K + Examples of alkaline earth metal ions constituting the alkaline earth metal salt include Mg 2+The metal ion (positive ion) constituting the metal salt is preferably Li + , K + 、Na + or Mg 2+ The negative ion constituting the metal salt is, for example, at least one selected from the group consisting of bis(fluorosulfonyl)imide ions, bis(trifluoromethanesulfonyl)imide ions (TFSI ions), tetrafluoroborate ions, and perchlorate ions, preferably at least one selected from the group consisting of bis(fluorosulfonyl)imide ions and bis(trifluoromethanesulfonyl)imide ions (TFSI ions).
[0073] (Method for producing electrolyte)
[0074] An example of a method for manufacturing the electrolyte according to the first embodiment is described. The method for manufacturing the electrolyte according to the first embodiment includes: a step of preparing an electrolyte solution including a metal salt and a medium (electrolyte solution preparation step); and a step of impregnating a porous insulator having pores with the electrolyte solution (impregnation step).
[0075] - Electrolyte preparation process -
[0076] The electrolyte solution preparation step prepares an electrolyte solution including a metal salt and a medium.
[0077] -Impregnation process-
[0078] The impregnation step impregnates the porous insulator having pores with the electrolyte. Thus, the pores of the porous insulator are filled with the electrolyte. When the prepared electrolyte is not liquid at room temperature (25° C.) (e.g., solid, quasi-solid (more specifically, a solid mixed in a liquid)), the electrolyte can be heated and impregnated in the porous insulator in a liquid state.
[0079] <Second embodiment: Battery>
[0080] The battery according to the second embodiment includes the electrolyte according to the first embodiment. The battery according to the second embodiment may further include a positive electrode and a negative electrode in addition to the electrolyte.
[0081] In the battery according to the present embodiment, the positive electrode includes a material constituting the positive electrode (more specifically, a positive electrode active material, etc.). The negative electrode includes an alkali metal (more specifically, Li, Na, K) or an alkaline earth metal (more specifically, Mg) as a material constituting the negative electrode (specifically, a negative electrode active material). The negative electrode includes, for example, a single body (more specifically, a plate, foil, and layer) of an alkali metal or an alkaline earth metal and a compound thereof.
[0082] The battery according to this embodiment can be configured as a secondary battery. Figure 1A conceptual diagram showing this situation. As shown in the figure, during charging, metal ions (Mn + (M represents a metal element, and n represents a positive integer): More specifically, Li + 、Na + , K + Mg 2+ The metal ions move from the positive electrode 10 to the negative electrode 11 through the electrolyte 12, thereby converting electrical energy into chemical energy and storing electricity. During discharge, the metal ions return from the negative electrode 11 to the positive electrode 10 through the electrolyte 12, thereby generating electrical energy.
[0083] The battery involved in the second embodiment can be used as a driving power source or auxiliary power source for, for example, a notebook computer, a PDA (portable information terminal), a mobile phone, a smart phone, a cordless phone, a camcorder, a digital still camera, an electronic book, an electronic dictionary, a portable music player, a radio, a headset, a game console, a navigation system, a memory card, a pacemaker, a hearing aid, an electric tool, an electric shaver, a refrigerator, an air conditioner, a television receiver, a stereo, a water heater, a microwave oven, a dishwasher, a washing machine, a dryer, a lighting device, a toy, a medical device, a robot, a load regulator, a signal light, a railway vehicle, a golf cart, an electric cart and / or an electric vehicle (including a hybrid vehicle). In addition, it can be mounted as a power storage power source for buildings represented by residences or power generation equipment, or used to supply power to them. In an electric vehicle, a conversion device that converts electric power into a driving force by supplying electric power is generally a motor. As a control device (control unit) that performs information processing related to vehicle control, a control device that displays the remaining battery amount based on information related to the remaining battery amount is included. In addition, the battery can also be used as a power storage device in a so-called smart grid. Such a power storage device can not only supply power, but also store power by receiving power from other power sources. As other power sources, for example, thermal power generation, nuclear power generation, hydropower generation, solar cells, wind power generation, geothermal power generation and / or fuel cells (including biofuel cells) can be used.
[0084] Although the embodiments of the present disclosure have been described above, these are merely typical examples, and therefore, the present disclosure is not limited thereto, and it is easily understood by those skilled in the art that various embodiments can be considered without changing the gist of the present disclosure.
[0085] For example, the composition of the electrolyte, the raw materials used in the manufacture, the manufacturing method, the manufacturing conditions, the characteristics of the electrolyte, the structure or construction of the battery are illustrative, not limited to these, and can be appropriately changed. For example, as a battery, in addition to a lithium battery, a magnesium battery, a sodium battery, and a potassium battery, an air battery and a fuel cell can also be listed.
[0086] Example
[0087] Hereinafter, the present disclosure will be described in more detail using examples, but the present disclosure is not limited to these examples.
[0088] <Example 1>
[0089] [1-1. Preparation of electrolyte]
[0090] (1-1. Raw materials)
[0091] The following raw materials were used.
[0092] - Porous insulator: Zeolite -
[0093] Fujifilm Wako Pure Chemical Industries, Ltd. "HS-320" (crystal system: Y-type, Si / Al ratio = 5.5, cationic species: H; hereinafter also referred to as "HS-320 (H)")
[0094] Fujifilm Wako Pure Chemical Industries, Ltd. "HS-320" (crystal system: Y-type, Si / Al ratio = 5.5, cation species: Na; hereinafter also referred to as "HS-320 (Na)")
[0095] Fujifilm Wako Pure Chemical Industries, Ltd. "HS-642" (crystal system: mordenite, Si / Al ratio = 18, cation species: Na)
[0096] Fujifilm Wako Pure Chemical Industries, Ltd. "HS-690" (crystal system: mordenite, Si / Al ratio = 180, cationic species: H)
[0097] · Tosoh Corporation "HSZ-360HUA" (crystal system: Y type, Si / Al ratio = 15, cationic species: H)
[0098] · Tosoh Corporation "HSZ-385HUA" (crystal system: Y type, Si / Al ratio = 100, cationic species: H)
[0099] · "HSZ-640HOA" manufactured by Tosoh Corporation (crystal system: mordenite, Si / Al ratio = 18, cation species: H)
[0100] · "HSZ-840HOA" manufactured by Tosoh Corporation (crystal system: ZSM-5, Si / Al ratio = 40, cation species: H)
[0101] · "HSZ-890HOA" manufactured by Tosoh Corporation (crystal system: ZSM-5, Si / Al ratio = 1500, cationic species: H)
[0102] · "HSZ-980HOA" manufactured by Tosoh Corporation (crystal system: beta, Si / Al ratio = 500, cationic species: H)
[0103] - Porous insulator: Mesoporous silica -
[0104] · "MCM-41" manufactured by Sigma-Aldrich
[0105] · "MCM-48" manufactured by Sigma-Aldrich
[0106] · "SBA-15" manufactured by Sigma-Aldrich
[0107] · "SBA-16" manufactured by Sigma-Aldrich
[0108] It should be noted that these four types of mesoporous silica do not contain Al artificially and are substantially composed of silicon dioxide (SiO 2 ). Therefore, it can be considered that the Si / Al ratio of these mesoporous silicas is at least greater than 10,000.
[0109] -Metal Salts-
[0110] Lithium bis(fluorosulfonyl)imide (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "LiFSI")
[0111] Lithium bis(trifluoromethanesulfonyl)imide (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "LiTFSI")
[0112] Lithium hexafluorophosphate (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "LiPF6" or "LiPF6")
[0113] Lithium tetrafluoroborate (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "LiBF4" or "LiBF4")
[0114] · Lithium perchlorate (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "LiClO4" or "LiClO4"
[0115] - Medium: Nitrile medium -
[0116] Succinonitrile (manufactured by Tokyo Chemical Industry Co., Ltd.; hereinafter also referred to as "SN")
[0117] Glutaronitrile (manufactured by Tokyo Chemical Industry Co., Ltd.; hereinafter also referred to as "GLN")
[0118] Adiponitrile (manufactured by Tokyo Chemical Industry Co., Ltd.; hereinafter also referred to as "AGN")
[0119] (1-2. Preparation of solid electrolyte)
[0120] LiFSI as a metal salt and succinonitrile SN as a medium were mixed at a molar ratio (medium / metal salt) of 4.0 to prepare an electrolyte solution.
[0121] HS-690, which is a porous insulator, is dried under vacuum at 300°C. The prepared electrolyte is impregnated in the dried HS-690, and the electrolyte is inserted (insert) and filled in the pores of the HS-690. A powdered solid electrolyte is thus prepared. The impregnation treatment is performed by mixing the electrolyte and the porous insulator by hand using a mortar and pestle. The impregnation amount (volume) of the electrolyte is set to an amount that is 100% relative to the previously measured micropore volume of the porous insulator (HS-690).
[0122] The preparation of the solid electrolyte was carried out in a glove box under an argon atmosphere.
[0123] (1-3. Preparation of measurement unit)
[0124] The prepared powdered solid electrolyte was punched at 200 MPa using a uniaxial press ("CDM-20PA" manufactured by Riken Kikai Co., Ltd.). As a stamping die for stamping, a die made of PET resin with upper and lower punches was used. In detail, the die made of PET resin has a cylindrical shape and has a cylindrical through opening along the center axis. The punch has a cylindrical shape and is configured to be plugged in and out of the through opening of the die, and is configured so that the front end faces (surfaces perpendicular to the insertion direction) of the upper and lower punches are opposed. The powdered solid electrolyte is arranged in the through opening of the die in a manner clamped by the front end faces of the upper and lower punches. The upper and lower punches are punched using a uniaxial press, thereby forming the solid electrolyte. In addition, a measuring unit (a unit for measuring) is made by directly using the upper punch and the lower punch of the die made of PET resin as blocking electrodes.
[0125] It should be noted that the process of manufacturing the measurement cell was performed in a glove box in an argon atmosphere.
[0126] [2. Measurement method and evaluation method]
[0127] (2-1. Form of electrolyte)
[0128] The appearance of the electrolyte (electrolyte composed of a metal salt and a medium) obtained in the preparation process of the solid electrolyte was visually observed. In addition, the container containing the electrolyte was tilted and the behavior of the liquid level changing parallel to the horizontal plane was visually observed. Based on these observations, the following evaluation criteria were used for determination.
[0129] (Evaluation Criteria)
[0130] Liquid: When a cylindrical container containing an electrolyte and a liquid or solid substance that is not mixed is tilted so that the bottom of the container is 30 degrees from the horizontal plane, the surface of the electrolyte becomes parallel to the horizontal plane within less than 1 second from the start of tilting.
[0131] Sherbet: When a cylindrical container containing electrolyte and a mixture of liquid and solid is tilted so that the bottom of the container is 30 degrees from the horizontal plane, the surface of the electrolyte becomes parallel to the horizontal plane within 1 second or more and 60 seconds after tilting.
[0132] Treacle-like: When a cylindrical container with a high-viscosity liquid appearance and electrolyte is placed in a tilted state so that the bottom of the container is 30 degrees to the horizontal plane, the shape of the electrolyte surface changes within 1 second or more and 60 seconds after the tilt, but the electrolyte surface does not become parallel to the horizontal plane.
[0133] Solid: When a cylindrical container that appears solid and contains electrolyte is tilted so that the bottom of the container is 30 degrees from the horizontal plane, the liquid level of the electrolyte does not change even if more than 10 minutes have passed since the tilt.
[0134] (2-2. Measurement of ion conductivity)
[0135] - Preparation of test samples -
[0136] The measurement cell produced in (1-3. Production of measurement cell) was sealed in the laminate with tab electrodes to prepare a cell for measuring ion conductivity as a measurement sample.
[0137] - Determination of ionic conductivity -
[0138] The ionic conductivity of the sample was measured using an impedance meter (VMP3 manufactured by Biologic). The ionic conductivity was measured using an AC impedance method at room temperature (25°C). The molar ratio (SN / LiFSI) of the solid electrolyte of Example 1 was 4.0, and the ionic conductivity was 4.9×10 -4 (S / cm). The results are shown in Table 1 together with the results of the above-mentioned observation of the appearance of the electrolyte. Table 1 shows the molar ratio (SN / LiFSI), the state of the electrolyte at room temperature, and the ion conductivity at room temperature.
[0139] (2-3. Structural analysis of electrolytes based on Raman spectroscopy)
[0140] The electrolytes of Examples 2 to 3 and 5 to 7 and Comparative Example 1 described below were subjected to structural analysis using Raman spectroscopy.
[0141] The solid electrolyte formed in (1-3. Preparation of the measuring unit) is used as a measuring sample for structural analysis. The obtained measuring sample is set in a microscopic laser Raman spectrometer ("LabRam HREvolution" manufactured by Horiba, Ltd.). The surface of the measuring sample is irradiated with an infrared laser (wavelength 1064nm), and the Raman spectrum is measured using an objective lens with a spot diameter of 7μm. It should be noted that the Raman spectrum can be measured by irradiating the cut surface formed by cutting the measuring sample (solid electrolyte) for structural analysis with an infrared laser.
[0142] Figure 3 The electrolytes of Examples 2 to 3, 5 to 7 and Comparative Example 1 have a range of 2220 to 2320 cm -1 Raman spectra under Figure 3 In the Raman spectrum shown, the vertical axis represents the Raman intensity (unit: arbitrary intensity) and the horizontal axis represents the Raman shift (unit: cm -1 ). Figure 3 The Raman spectrum shown has a peak at 2254 cm -1 The peaks near and at 2280cm -1 Nearby peak. Located at 2280cm -1 The peaks near 2254 cm-1 are attributed to the CN stretching vibration of the nitrile group of SN. -1 A peak whose nearby peaks are shifted to the high wavenumber side.
[0143] (2-4. Determination of Si / Al ratio by nuclear magnetic resonance method)
[0144] In Examples 11 to 19 described below, the Si / Al ratio of zeolite or mesoporous silica was determined.
[0145] Specifically, the zeolite or mesoporous silica is crushed to a degree that can be measured. The crushed zeolite or mesoporous silica is placed in a nuclear magnetic resonance device ("ECA400 FT-NMR device" manufactured by JEOL Ltd.). At a magnetic field strength of 9.2 T and nuclides: 29 The measurement was carried out under the conditions of Si measurement, and the result was 29 Si NMR spectrum. 29 The peak area intensity ratio of the Si NMR spectrum yields the Si / Al ratio.
[0146] <Examples 2 to 9 and Comparative Examples 1 to 2: Molar ratio>
[0147] The electrolyte was prepared in the same manner as in Example 1, except that the molar ratio (SN / LiFSI) was changed from 4.0 to the molar ratio described in Table 1, and the ion conductivity was measured. In addition, the appearance of the electrolyte solution obtained in the electrolyte preparation step was also observed. These results are shown in Table 1.
[0148] It should be noted that, when the concentration of the metal salt in the electrolyte composed of the metal salt and the medium is relatively high (i.e., when the concentration of the medium is relatively low), the electrolyte sometimes becomes a solid or a liquid with solid precipitated at room temperature (25°C). In this case, the electrolyte is heated until the solid in the prepared electrolyte is completely dissolved (e.g., 90°C), and the immersion treatment is performed after the liquid is formed.
[0149] In Example 6, a Li4Ti5O 12 A lithium ion secondary battery with LiFePO4 as the positive electrode was used. The battery was charged and discharged at a current of 0.1C (coulomb). The charge and discharge potential was about 1.8V.
[0150] [Results: Examples 1 to 9 and Comparative Examples 1 to 2: molar ratio]
[0151] (Ionic conductivity)
[0152] Table 1 shows the molar ratio (SN / LiFSI) and the ion conductivity at room temperature. Figure 2 . Figure 2 The relationship between the molar ratio (SN / LiFSI) and the ionic conductivity at room temperature is shown. Figure 2 The horizontal axis represents the molar ratio, and the vertical axis represents the ionic conductivity at room temperature (unit: S / cm). Figure 2 For example, 1.0E-03 represents 1.0×10 -3 .
[0153] [Table 1]
[0154]
[0155] *1: Succinonitrile, *2: Lithium bis(fluorosulfonyl)imide,
[0156] *3: Electrolyte consisting of metal salt and medium used in each example
[0157] In the electrolyte of SN-LiFSI system, Figure 2As shown, as the molar ratio (SN / LiFSI) increases from 0.1 to 0.5, the ionic conductivity at room temperature simply increases, as the molar ratio (SN / LiFSI) increases from 0.5 to 4.0, the ionic conductivity at room temperature simply decreases, and as the molar ratio (SN / LiFSI) increases from 6.0 to 10.0, the ionic conductivity at room temperature is approximately the same value.
[0158] In addition, the ionic conductivity of the electrolyte solution composed of SN and LiFSI in Examples 2 and 3 was measured, and the results were all below the lower limit of measurement (or below the measurement limit; more specifically, about 10 -7 S / cm). This is a value equivalent to the ionic conductivity of an insulator.
[0159] (Bridge Structure)
[0160] In the electrolyte of SN-LiFSI system, Figure 3 As shown in Figure 2, when the molar ratio (SN / LiFSI) is 10.0, the peak (Raman scattering peak) derived from the stretching vibration of CN is located at 2254 cm -1 When the molar ratio (SN / LiFSI) decreases to 0.3 to 0.8 and 1.5 to 2.0, it is located at 2254 cm -1 The peak intensity near 2280cm -1 A peak appears near , and the peak intensity on the high wave number side increases relatively. In the electrolytes of Examples 2 to 3 and Examples 5 to 7, the peak derived from CN stretching vibration shifts to the high wave number side compared to the electrolyte of Comparative Example 1.
[0161] Based on these results, it can be considered that in the electrolytes of Examples 2 to 3 and Examples 5 to 7, Li + It forms a bridge structure with SN as a medium. It can be inferred that the bridge structure is based on a specific molar ratio (SN / LiFSI).
[0162] [Comparison between Examples 1 to 9 and Comparative Examples 1 to 2]
[0163] The electrolytes of Examples 1 to 9 include HS-690 as a porous insulator having pores, SN as a medium having two nitrile groups arranged in the pores, and LiFSI as a metal salt, wherein the LiFSI as a metal salt is at least one selected from the group consisting of an alkali metal salt and an alkaline earth metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 4.0. That is, the electrolytes of Examples 1 to 9 are electrolytes included in the scope of the invention involved in Technical Solution 1.
[0164] The ionic conductivity of the electrolytes of Examples 1 to 8 is 4.1×10-4 ~85×10 -4 S / cm.
[0165] The electrolytes of Comparative Examples 1 and 2 are electrolytes not included in the scope of the invention according to Claim 1. Specifically, in the electrolytes of Comparative Examples 1 and 2, the molar ratio of the medium to the metal salt (medium / metal salt) exceeds 4.0.
[0166] The ion conductivity of the electrolytes of Comparative Examples 1 and 2 was 1.5×10 -4 ~2.0×10 -4 S / cm.
[0167] Examples 1 to 9 included in the scope of the invention according to claim 1 have higher ion conductivity at normal temperature (room temperature) than Comparative Examples 1 to 2 not included in the scope of the invention according to claim 1. This shows that the invention according to claim 1 is excellent in ion conductivity.
[0168] <Examples 11 to 19: Porous insulator (zeolite)>
[0169] An electrolyte was prepared in the same manner as in Example 1, except that HS-690 as the porous insulator and the molar ratio were changed to the porous insulator (zeolite) and the molar ratio described in Table 2, respectively, and a battery was produced.
[0170] In addition, the ion conductivity was measured in the same manner as in Example 1. Table 2 shows the results.
[0171] [Table 2]
[0172]
[0173]
[0174] *1: Acrylonitrile, *2: Lithium bis(fluorosulfonyl)imide
[0175] The electrolytes of Examples 11 to 19 include any one of HS-320 (H), HS-320 (Na), HSZ-360HUA, HSZ-640HOA, HS-642, HSZ-840HOA, HSZ-385HUA, HSZ-980HOA, and HSZ-890HOA as porous insulators (zeolites) having pores, and SN as a medium having two nitrile groups arranged in the pores, and LiFSI as a metal salt, wherein the LiFSI as a metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 4.0. That is, the electrolytes of Examples 11 to 19 are electrolytes included in the scope of the invention involved in Technical Solution 1.
[0176] In addition, the ion conductivity of the electrolytes of Examples 11 to 19 was 8.0×10 -4 ~46×10 -4 S / cm increases with the increase of Si / Al ratio. This tendency indicates that the larger the Si / Al ratio, the more silanol groups exist in the pore walls of the porous insulator (zeolite), and as a result, the carrier (Li + )’s jumping sites increase.
[0177] <Examples 31 to 36: Metal salt and medium>
[0178] The electrolyte was prepared in the same manner as in Example 1, and a battery was produced, except that LiFSI as the metal salt, SN as the medium, and the molar ratio (SN / LiFSI) were changed to the metal salt, medium, and molar ratio (medium / alkali metal salt) described in Table 3, respectively. In addition, the ion conductivity was measured in the same manner as in Example 1. The results are shown in Table 3.
[0179] [Table 3]
[0180]
[0181]
[0182] *1: Lithium bis(trifluoromethanesulfonyl)imide, *2: Lithium hexafluorophosphate, *3: Lithium tetrafluoroborate, *4: Lithium perchlorate, *5: Lithium bis(fluorosulfonyl)imide, *6: Acrylonitrile, *7: Glutaronitrile, *8: Adiponitrile
[0183] The electrolytes of Examples 31 to 36 include HS-690 as a porous insulator having pores, any one of SN, GLN and ADN as a medium having two nitrile groups arranged in the pores, and any one of LiTFSI, LiPF6, LiBF4, LiClO4 and LiFSI as a metal salt, wherein the metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 4.0. That is, the electrolytes of Examples 31 to 36 are electrolytes included in the scope of the invention involved in Technical Solution 1.
[0184] <Examples 41 to 48: Porous insulator (mesoporous silica)>
[0185] An electrolyte was prepared in the same manner as in Example 1, and a battery was produced, except that HS-690 as the porous insulator was changed to a porous insulator (mesoporous silica) described in Table 4.
[0186] In addition, the ion conductivity was measured in the same manner as in Example 1. Table 4 shows these results.
[0187] [Table 4]
[0188]
[0189] *1: Acrylonitrile, *2: Lithium bis(fluorosulfonyl)imide
[0190] The electrolyte of Examples 41 to 48 comprises any one of MCM-48, SBA-15, MCM-41 and SBA-16 as a porous insulator having pores, SN as a medium having two nitrile groups arranged in the pores, and LiFSI as a metal salt, wherein the metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 4.0. The electrolytes of Examples 41 to 48 are electrolytes included in the scope of the invention involved in Technical Solution 1.
[0191] The electrolyte and battery according to the present disclosure are described below.
[0192] <1> An electrolyte,
[0193] A porous insulator having pores, a medium having two nitrile groups and a metal salt arranged in the pores,
[0194] The metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts,
[0195] The molar ratio of the medium to the metal salt (medium / metal salt) is 0.1 or more and 4.0 or less.
[0196] <2> The electrolyte according to <1>, wherein the medium is at least one selected from the group consisting of succinonitrile, glutaronitrile, and adiponitrile.
[0197] <3> The electrolyte according to <1> or <2>, wherein the metal salt is a lithium salt.
[0198] <4> The electrolyte according to any one of <1> to <3>, wherein the porous insulator is at least one selected from the group consisting of zeolite and mesoporous silica.
[0199] <5> The electrolyte according to any one of <1> to <4>, wherein the positive ions constituting the metal salt are Li + , K + 、Na + or Mg 2+ .
[0200] <6> The electrolyte according to any one of <1> to <5>, wherein the negative ions constituting the metal salt are at least one selected from the group consisting of bis(fluorosulfonyl)imide ions and TFSI ions.
[0201] <7> The electrolyte according to any one of <1> to <6>, which is a solid electrolyte.
[0202] <8> The electrolyte according to any one of <1> to <7>, wherein the medium is at least one nitrile-based medium selected from the group consisting of succinonitrile, glutaronitrile and adiponitrile,
[0203] In the Raman spectrum, the peak derived from the CN stretching vibration of the nitrile group is shifted to a higher wave number side.
[0204] <9> The electrolyte according to any one of claims 1> to <8>, wherein the porous insulator is at least one selected from the group consisting of zeolite and mesoporous silica,
[0205] The Si / Al ratio of the zeolite and the mesoporous silica is 5 or more.
[0206] <10> A battery comprising the electrolyte according to any one of <1> to <9>.
[0207] Industrial Applicability
[0208] The battery including the electrolyte according to the present disclosure can be used in various fields where electricity storage is envisioned. Although merely illustrative, batteries (particularly secondary batteries) having the electrolytes disclosed herein can be used in: electrical, information, and communication fields using electrical and electronic devices, etc. (for example, electrical and electronic equipment fields or mobile equipment fields including small electronic devices such as mobile phones, smart phones, laptop computers, digital cameras, activity meters, wristband computers, electronic paper, wearable devices, RFID tags, card-type electronic money, and smart watches); household and small industrial uses (for example, power tools, golf carts, and household, nursing, and industrial robots); large industrial uses (for example, forklifts, elevators, and bay cranes); transportation system fields (for example, hybrid vehicles, electric vehicles, buses, trams, electric-assisted bicycles, electric motorcycles, etc.); power system uses (for example, various power generation, load regulators, smart grids, and general household-installed power storage systems); medical uses (medical equipment such as headphones and hearing aids); pharmaceutical uses (dose management systems, etc.); and IoT fields; space and deep-sea uses (for example, space probes, submersible research vessels, etc.), etc.
Claims
1. An electrolyte comprising: A porous insulator having pores; and A medium having two nitrile groups and a metal salt disposed in the pores, The metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts, The molar ratio of the medium to the metal salt, that is, medium / metal salt, is 0.1 or more and 4.0 or less.
2. The electrolyte according to claim 1, wherein The medium is at least one selected from the group consisting of succinonitrile, glutaronitrile and adiponitrile.
3. The electrolyte according to claim 1 or 2, wherein The metal salt is a lithium salt.
4. The electrolyte according to any one of claims 1 to 3, wherein The porous insulator is at least one selected from the group consisting of zeolite and mesoporous silica.
5. The electrolyte according to any one of claims 1 to 4, wherein The positive ion constituting the metal salt is Li + , K + 、Na + or Mg 2+ .
6. The electrolyte according to any one of claims 1 to 5, wherein The negative ion constituting the metal salt is at least one selected from the group consisting of bis(fluorosulfonyl)imide ions and bis(trifluoromethanesulfonyl)imide ions.
7. The electrolyte according to any one of claims 1 to 6, wherein The electrolyte is a solid electrolyte.
8. The electrolyte according to any one of claims 1 to 7, wherein The medium is at least one nitrile medium selected from the group consisting of succinonitrile, glutaronitrile and adiponitrile, In the Raman spectrum, the peak derived from the CN stretching vibration of the nitrile group is shifted to a higher wave number side.
9. The electrolyte according to any one of claims 1 to 8, wherein The porous insulator is at least one selected from the group consisting of zeolite and mesoporous silica. The Si / Al ratio of the zeolite and the mesoporous silica is 5 or more. 10 . A battery comprising the electrolyte according to claim 1 .
